CO-INFECÇÃO POR Leishmania sp. EM INDIVÍDUOS VIVENDO COM HIV/Aids - Carvalho, Flávia Lopes (2009)
Co-infection Leishmania-HIV/Aids is a serious public health problem in almost of the world. The visceral leishmaniasis is the clinical form of leishmaniosis hat is most associated with HIV/Aids cases being the co-infection understated, since the leishmaniasis is not AIDS-defining illness. This was a descriptive cross sectional study from March 2006 to December 2008, aiming to investigate the occurrence of co-infection Leishmania-HIV in individuals living with HIV/Aids in a Reference Center in São Luís-MA. The population studied was composed of 287 individuals. It was used a questionnaire to collect demographic, epidemiological and socioeconomic data. The physical examination was performed and biological material for detection of infection by Leishmania chagasi was collected by indirect immunofluorescence technique (IIFT), and laboratory tests (blood count, CD4 and CD8, viral load, myelography) were found in charts. We used the chi-square test to assess association of demographic, socioeconomic and epidemiological variables between women and men, whereas p ≥ 0.05 for significance. Women and men had a statistically significant difference in color, destination of waste, occupation and family income. The presence of pen and near the residence showed statistically significant differences when comparing men and women. The prevalence of infection with Leishmania sp, detected by Montenegro Skin Test (MST) was 1,4%. All co-infected showed RIFI and as well as the bone marrow aspirate (myelogram) positives. This study helped identify the magnitude of the prevalence of co-infection Leishmania/HIV. Thus, we suggest that the anti-Leishmania has to be part of the differential diagnosis of individuals with HIV / AIDS and those public policies are increased for this problem.